Formalisation and verification of interaction protocols for business process integration: a Petri net approach. (10th March 2009) - Benmerzoug, Djamel; Kordon, Fabrice; Boufaida, Mahmoud
Interaction Protocols (IP) are specific, often standard, constraints on the behaviours of the autonomous agents in a multiagent system. Protocols are essential to the functioning of open business systems, such as those that arise in most interesting web applications. This paper presents a new approach for Business Process Integration (BPI) based on IP. It enables both integration and collaboration of autonomous and distributed business processes modules. We present a semantic formalisation of the IP notations used in our approach. The semantics and its application are described on the basis of translation rules to Coloured Petri Nets (CPNs) and the benefits of formalisation are shown.